- Thread starter
- #1

- Thread starter skoker
- Start date

- Thread starter
- #1

- Jan 29, 2012

- 661

Rightlet A be a non singular matrix. then \(A^2=A, \quad A^{-1}A^2=A^{-1}A, \quad IA=I, \quad A=I\)

Why do you write this? $A^2=A$ just by hypothesis.therefore \(A^2=A.\)

- Thread starter
- #3

i suppose that is redundant or unnecessary. i was not sure if it needs a conclusion with the 'therefore'.Right

Why do you write this? $A^2=A$ just by hypothesis.

- Jan 26, 2012

- 890

The therfore should go before the \(A=I\) and you should stop at that point.i suppose that is redundant or unnecessary. i was not sure if it needs a conclusion with the 'therefore'.

CB